The same, only different: estimating the magnitude of bribery in business surveys - Frédéric Lesné (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
As first shown in Clarke (2011), Word Bank's Enterprise Surveys data suggest that the magnitude of bribery estimated by firm owners and managers in Africa is considerably higher when estimates are formulated as a percentage of turnover rather than in monetary value. This working paper confirms these findings with a randomized experiment carried out in Madagascar with 436 firm owners and managers and provides additional evidence that the observed gap in estimates between these two answer formats is caused by a measurement error on the part of survey respondents. Experience in running a business appears to mitigate error but without eliminating it completely.
Keywords: 330